The Role of Fomo in Mediating The Effect of Hedonic Shopping Motivation and Discounts on Impulsive Buying on The Shopee Platform - Dewa Gede Putra Sudiarta; IA Oka Martini (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
Changes in the shopping behavior of digital society, particularly Generation Z, show an increase in impulsive buying that occurs spontaneously without careful planning, triggered by ease of access, attractive promotions, and e-commerce features such as those on Shopee that offer fast and seamless transactions. The selection of Denpasar City as the research location is based on its relevance as an economic center with a high proportion of Generation Z and a community that is adaptive to digital technology, making it relevant to examine hedonic shopping motivation, discounts, FOMO, and impulsive buying. The purpose of this study is to identify the effect of each variable, including hedonic shopping motivation, discounts, FOMO, and impulsive buying on the Shopee platform. This study used 115 respondents. The data were then processed using SmartPLS 3 software. The type of data used in this study is quantitative data, with data sources consisting of secondary data and primary data. The data collection technique used a questionnaire distribution, and the data analysis techniques included validity testing, reliability testing, measurement model (outer model), structural model (inner model), and hypothesis testing. The conclusion of this study is that hedonic shopping motivation has a positive and significant effect on FOMO, discounts have a positive and significant effect on FOMO, hedonic shopping motivation has a positive and significant effect on impulsive buying, discounts have a positive and significant effect on impulsive buying, FOMO has a positive and significant effect on impulsive buying, FOMO significantly mediates the relationship between hedonic shopping motivation and impulsive buying, and FOMO also significantly mediates the effect of discounts on impulsive buying. Suggestions for future research include paying attention to the lowest indicators so they can be improved in the future, and expanding the number and variety of respondents so that the results obtained can represent consumer conditions more accurately.